IMPLEMENTING THE GAMIFICATION LEARNING METHOD TO IMPROVE LEARNING RESULTS OF ADJUSTING JOURNAL - Nur Hida Aulia Majid; Endra Murti Sagoro (Universitas Negeri Yogyakarta, 2018)
This study aims to improve Cognitive Learning Results of Adjusting Journal through implementing The Gamification Learning Method. The study also test the effectiveness of gamification learning method compare with teacher-centered. The subject of this study were 30 students of grade X Accounting 2 of SMK Negeri 1 Wonosari in the academic year of 2017/2018. This was an Experimented Classroom Action Research conducted in two cycles. The data was collected through tests, field notes, observation, and documentation. Data analysis used were independent sample t-test, paired sample t-test, descriptive data analysis of quantitative and qualitative. Based on the results of research, implementing The Gamification Learning Methods can improve Learning Results of Adjusting Journal. It can be seen from the average percentage of pre-test results 48.27, post-test I 64.57 and post-test II to 80.27 at significance value of 0.000. The Gamification Learning Method is also more effective than the teacher-centered method as shown by Independent Sample T-Test at significance value of 0.031. Keywords: Gamification Learning Method, Learning Results, CAR